European Real Estate Society, 2005 - D'Arcy, Éamonn (Journal of property investment & finance ;, 2006)
This e-book presents prize winning papers presented at the Dublin European Real Estate Society conference, the worlds largest real estate research conference in terms of both participation and papers presented. The first paper is the winner of the third annual Gerald Brown Memorial Prize, sponsored by Emerald, for the best paper presented in the area of Commercial Real Estate Investment and Finance - "Real Estate Value: Creation and Destruction" by Stephen Roulac, Alastair Adair, Stanley McGreal, Jim Berry and Suzanne Allen from the University of Ulster